Assessment of risk investments focused on the market - A. F. Gribov (Путеводитель предпринимателя, 2020)
In Modigliani-Miller’s model recognize that the investor isn’t taxed. Besides, at a number of the assumptions it is declared that the structure of sources of financing of the estimated investment project, in particular, a ratio between own and loan capital doesn’t matter. If to include both of these aspects in the analysis, then there is a number of important and interesting problems which are discussed in this article.